An Inverter-Based, CMOS, Low-Power Optical Receiver Front-End. Issue 1 (2nd January 2019) - Zohoori, Soorena; Dolatshahi, Mehdi; Pourahmadi, Majid; Hajisafari, Mahmoud
ABSTRACT: In this paper, a low-power optical receiver front-end which consists of a transimpedance amplifier (TIA) and three stages of limiting amplifier (LA) for 2.5 Gb/s applications is proposed in 0.18 µm CMOS technology. The proposed TIA benefits from a modified inverter structure, in which the input resistance is properly reduced due to the use of diode-connected transistors in comparison with conventional inverter circuit. Also, an active inductor is used in parallel with a diode-connected transistor at the output node, which provides a low output resistance, while it resonates with the load capacitance to extend the −3 dB frequency bandwidth. Moreover, three stages of LAs are used to obtain extra gain, in which each LA cell uses active inductor load. However, HSPICE simulations for the proposed TIA circuit show a 42.24 dBΩ transimpedance gain, 1.96 GHz frequency bandwidth, 11.7 pA/√Hz input referred noise, and only 972 µW of power consumption at 1.5 V supply. Also, simulation results for the whole receiver system show a 75.6 dB gain, 1.7 GHz frequency bandwidth, and 6.54 mW of power consumption at 1.5 V supply. Finally, simulation results indicate that the proposed receiver system has good performances to be used as a low-power optical receiver front-end.